An independent and external validation of QRISK2 cardiovascular disease risk score: a prospective open cohort study - Collins, G; Altman, D (2010)
Objective: To evaluate the performance of the QRISK2 score for predicting 10-year cardiovascular disease in an independent UK cohort of patients from general practice records and to compare it with the NICE version of the Framingham equation and QRISK1. Design: Prospective cohort study to validate a cardiovascular risk score. Setting: 365 practices from United Kingdom contributing to The Health Improvement Network (THIN) database. Participants: 1.58 million patients registered with a general practice between 1 January 1993 and 20 June 2008, aged 35-74 years (9.4 million person years) with 71 465 cardiovascular events. Main outcome measures: First diagnosis of cardiovascular disease (myocardial infarction, angina, coronary heart disease, stroke, and transient ischaemic stroke) recorded in general practice records. Results: QRISK2 offered improved prediction of a patient's 10-year risk of cardiovascular disease over the NICE version of the Framingham equation. Discrimination and calibration statistics were better with QRISK2. QRISK2 explained 33% of the variation in men and 40% for women, compared with 29% and 34% respectively for the NICE Framingham and 32% and 38% respectively for QRISK1. The incidence rate of cardiovascular events (per 1000 person years) among men in the high risk group was 27.8 (95% CI 27.4 to 28.2) with QRISK2, 21.9 (21.6 to 22.2) with NICE Framingham, and 24.8 (22.8 to 26.9) with QRISK1. Similarly, the incidence rate of cardiovascular events (per 1000 person years) among women in the high risk group was 24.3 (23.8 to 24.9) with QRISK2, 20.6 (20.1 to 21.0) with NICE Framingham, and 21.8 (18.9 to 24.6) with QRISK1. Conclusions: QRISK2 is more accurate in identifying a high risk population for cardiovascular disease in the United Kingdom than the NICE version of the Framingham equation. Differences in performance between QRISK2 and QRISK1 were marginal.